2015
DOI: 10.1128/mcb.01475-14
|View full text |Cite
|
Sign up to set email alerts
|

PATZ1 Is a DNA Damage-Responsive Transcription Factor That Inhibits p53 Function

Abstract: e Insults to cellular health cause p53 protein accumulation, and loss of p53 function leads to tumorigenesis. Thus, p53 has to be tightly controlled. Here we report that the BTB/POZ domain transcription factor PATZ1 (MAZR), previously known for its transcriptional suppressor functions in T lymphocytes, is a crucial regulator of p53. The novel role of PATZ1 as an inhibitor of the p53 protein marks its gene as a proto-oncogene. PATZ1-deficient cells have reduced proliferative capacity, which we assessed by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Consistent with the ability of PATZ1 to interact with p53 and regulate transcription of p53 target genes [10,13], we next showed that in PATZ1-expressing cells the EMT and cell migration gene program, activated by EGF and negatively regulated by p53, was deregulated. In more details, PATZ1 binds the promoter regions of three genes, EpCam, RhoE and Caldesmon, involved in EMT, cellular migration and invasion, respectively, modulating their transcriptional changes associated with EGF stimulation (Figure 1).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Consistent with the ability of PATZ1 to interact with p53 and regulate transcription of p53 target genes [10,13], we next showed that in PATZ1-expressing cells the EMT and cell migration gene program, activated by EGF and negatively regulated by p53, was deregulated. In more details, PATZ1 binds the promoter regions of three genes, EpCam, RhoE and Caldesmon, involved in EMT, cellular migration and invasion, respectively, modulating their transcriptional changes associated with EGF stimulation (Figure 1).…”
Section: Introductionmentioning
confidence: 56%
“…Consistently, silencing of PATZ1 expression in a p53-null osteosarcoma cell line enhanced its sensitivity to the proapoptotic chemotherapeutic agent 5-fluorouracil (5FU), while Patz1-/-mouse embryonic fibroblasts show a decreased number of apoptotic cells, either spontaneous or induced by 5FU treatment, compared with wild-type controls [10]. However, in a colon cancer cell line, even in the presence of a wild-type p53, PATZ1 has been shown to inhibit p53 function [13], supporting the concept that PATZ1 may have opposite roles on p53 in different tumors. In this context, our recent studies show that PATZ1 acts as a tumor suppressor in thyroid cancer via targeting p53-dependent genes involved in EMT and cell migration [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar fusion involving these two genes has been described once before in an undifferentiated sarcoma that presented in the chest wall of a teenager [33]. PATZ1 is a BTB-ZF transcription factor that inhibits the ability of p53 to bind to its response elements and is involved in keeping embryonic stem cells in an undifferentiated state [28,37]. Rearrangement of EWSR1 is found in intracranial Ewing sarcomas that involve the inner table of the skull and extraosseous meningeal ‘peripheral’ primitive neuroectodermal tumors [35,52].…”
Section: Discussionmentioning
confidence: 74%
“…PATZ1 also negatively regulates induced pluripotent stem-cell (iPSC) generation (Ow et al, 2014;Ma et al, 2014). This function may be related to its interaction with the p53 tumour suppressor, as demonstrated by various studies (Valentino, Palmieri, Vitiello, Pierantoni et al, 2013;Keskin et al, 2015;Chiappetta et al, 2015).…”
Section: Introductionmentioning
confidence: 94%